2017
DOI: 10.1001/jamasurg.2017.0904
|View full text |Cite|
|
Sign up to set email alerts
|

Centers for Disease Control and Prevention Guideline for the Prevention of Surgical Site Infection, 2017

Abstract: This guideline is intended to provide new and updated evidence-based recommendations for the prevention of SSI and should be incorporated into comprehensive surgical quality improvement programs to improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
2,187
10
157

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,558 publications
(2,373 citation statements)
references
References 23 publications
19
2,187
10
157
Order By: Relevance
“…( [1][2][3] Although the evidence is well defined, the adherence to these measures in hospital practice turns out to be a challenge due to the complexity of the system, the limitation of human resources, materials and equipment, workload, lack of knowledge, and inefficient management, among other factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…( [1][2][3] Although the evidence is well defined, the adherence to these measures in hospital practice turns out to be a challenge due to the complexity of the system, the limitation of human resources, materials and equipment, workload, lack of knowledge, and inefficient management, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) Among the HAIs, surgical site infection (SSI) has a prominent role, which can be manifested up to 30 days after surgery, or up to 90 days after if an implant is used, and are classifi ed according to the degree of involvement, namely: superfi cial incision, deep incision, or organ and/or space infection. (3,4) Surgical site infection is one of the main targets of epidemiological surveillance in health institutions. In underdeveloped and developing countries, it is estimated that SSI can aff ect up to onethird of patients undergoing surgical procedures and, although less frequent in industrialized countries, it is the second among the HAIs in Europe and the United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If hands are soiled, they should be washed again with an antiseptic surgical solution because although alcohol rapidly kills microorganisms, it does not physically remove organic material. Studies have shown that waterless chlorhexidine scrub is as effective as traditional waterbased scrubs and requires less time and having a persistent suppressive effect against bacterial regrowth on the skin, potentially lasting throughout several operations [1,2].…”
Section: Surgical Hand Scrubmentioning
confidence: 99%